The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1007/s00500-023-08189-7
|View full text |Cite|
|
Sign up to set email alerts
|

Interval-valued intuitionistic fuzzy symmetric point criterion-based MULTIMOORA method for sustainable recycling partner selection in SMEs

Abstract: The need and strategy of eco-economy encourage enterprises to reach sustainability by employing sustainable supply chain management. Contrary to the numerous literatures focusing on green design and sustainability practices, this paper presents sustainable recycling partner (SRP) assessment with economic, environmental and social pillars. To propose an integrated framework for SRP selection in small-and-medium enterprises (SMEs), interval-valued intuitionistic fuzzy set (IVIFS)based model is applied to deal wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…Earlier studies have suggested performing the sensitivity analysis via varying the input parameters to observe their effect on the original ranking, as subjectively fixed parameters in the evaluation process have a substantial influence on the original ranking (Hezam et al, 2023;Pamucar et al, 2023;Rani et al, 2023). Therefore, in this Similarly, for the remaining eight cases, the normal weight of the top-ranked ESG challenge was interchanged from 0.20000 to 0.90000…”
Section: Validation Testmentioning
confidence: 99%
“…Earlier studies have suggested performing the sensitivity analysis via varying the input parameters to observe their effect on the original ranking, as subjectively fixed parameters in the evaluation process have a substantial influence on the original ranking (Hezam et al, 2023;Pamucar et al, 2023;Rani et al, 2023). Therefore, in this Similarly, for the remaining eight cases, the normal weight of the top-ranked ESG challenge was interchanged from 0.20000 to 0.90000…”
Section: Validation Testmentioning
confidence: 99%